Diminished Treatment Response of Periodontally Diseased Patients Infected with the JP2 Clone of Aggregatibacter (Actinobacillus) actinomycetemcomitans - Cortelli, Sheila Cavalca; Costa, Fernando Oliveira; Kawai, Toshihisa; Aquino, Davi Romeiro; Nobre Franco, Gilson Cesar; Ohara, Kazuhisa; Roman-Torres, Caio Vinícius Gonçalves; Cortelli, José Roberto (Journal of Clinical Microbiology, 2009)
This longitudinal study evaluated the response to periodontal treatment by subjects infected with either JP2 (n = 25) or non-JP2 (n = 25) Aggregatibacter (Actinobacillus) actinomycetemcomitans. Participants were treated during the first 4 months by receiving (i) scaling and root planing, (ii) systemic antibiotic therapy, and (iii) periodontal surgery. Probing depth (PD), clinical attachment level (CAL), and gingival and plaque indices (GI and PI, respectively) were monitored at baseline and at 12 months, along with DNA-PCR-based subgingival detection of JP2 or non-JP2 A. actinomycetemcomitans. At baseline, PD, CAL, and GI scores were statistically higher in the JP2 strain-positive group than the non-JP2-strain-positive group. At 12 months, PD, CAL, and GI scores had decreased significantly for both groups, but the reduction rates of PD and CAL were higher in the non-JP2-strain-positive group. Among JP2-strain-positive patients in the baseline, patients who remained JP2 strain positive at 12 months showed significantly higher GIs than did the patients who had lost the detectable JP2 clone. Patients who remained JP2 strain positive at 12 months appeared to be more resistant to mechanical-chemical therapy than did those who were still non-JP2 strain positive, while the elimination of JP2 A. actinomycetemcomitans remarkably diminished gingival inflammation. Early identification and elimination of the JP2 clone of A. actinomycetemcomitans will enable practitioners to effectively predict the outcome of treatments applied to periodontal patients.